Postfire Damage Assessment of a RC Factory Building - Ada, Mehmet; Yuzer, Nabi; Ayvaz, Yusuf (ASCE-AMER SOC CIVIL ENGINEERS, 2019)
This paper presents an assessment of postfire damage of a RC factory building. The fire was limited to the ground floor; thus, the structural elements on the ground floor were fire damaged. Also, some relative displacements were observed at the expansion joints, and long wall cracks were observed on other stories. During the visual assessment, typical fire damage was observed (e.g., spalling, netlike cracks, crumbled plaster, bared or visible reinforcement, and crumbled aggregates). Also, some explosive and thermal expansion-induced damage was observed in and out of the fire-damaged areas. To evaluate the effects of the fire on the concrete, spectrophotometer and compressive strength tests were performed on concrete specimens taken from the building. It is concluded that elevated temperatures due to a fire can cause damage in the fire region, and that it can affect the overall stability of the structure.
Keywords: Elevated temperature; Fire damage; Compression strength; Reinforced concrete building; Concrete; REINFORCED-CONCRETE SLABS; HIGH-STRENGTH CONCRETE; HIGH-TEMPERATURE; FIRE RESISTANCE; BOND STRENGTH; BEHAVIOR; COLUMNS; PERFORMANCE; COVER; BEAMS; Construction & Building Technology; Engineering